Ethnographic Realism and the Role of the Ethnologist of Religion - Šantek, Goran-Pavel (Array, 2005)
On the basis of his own ethnographic experience in researching a particular religious movement, the author discusses the diverse contemporary concepts of field research and representations of field material. While not disputing the numerous advantages that they have brought to ethnography and its affirmation, their reverse side, possibly limiting to the ethnographer, is pointed out in the text. Going out into the field and entering into the social world of Others is stressed as being the fundamental ethnographic activity, which may, but need not, enable the uncovering of unknown processes of social life.